KNOWLEDGE SHARING AND ORGANIZATIONAL PERFORMANCE: AN EMPIRICAL INVESTIGATION - Reijeng Tabara (SOSCIED, 2022)
The purpose of this study was to determine the effect of Knowledge Sharing on organizational performance at the Religious Office of District X West Papua. This study uses Partial Least Squares (PLS) with Structural Equation Modeling (SEM) techniques to analyze 63 employees. The results showed that there was a positive and significant influence between Knowledge Sharing on organizational performance with a Tstatistic value greater than Ttable (Tstatistic 3.193 > Ttable 1.98) at a significance level of 5% (0.05). The results of this study indicate that the higher the Knowledge Sharing owned by the organization, it will further improve the performance of the Organization at the Religious Office of District X West Papua